„Misa Adat” – msza święta inkulturowana w regionie Manggarai na wyspie Flores (Indonezja) - Meka, Vinsensius Adi Gunawan (Annales Missiologici Posnanienses, 2012)
In Manggarai region, on the Flores island (Indonesia), was developed an interesting form of Mass adapted to the local culture. It has been named “Misa Adat”. In this article at first the author discusses the problem of “adat”. This tradition makes important reality in the spiritual life of people living there. The article makes an attempt of reflection on spiritual needs and the fruits of this adaptation. At the end the author points at the differences of such liturgy compared to the traditional form of liturgy of Eucharist described in the Roman Missal.